2017
DOI: 10.24966/ghr-2566/100007
|View full text |Cite
|
Sign up to set email alerts
|

A Physic Tensile Forces Experiment to Possible Explain the Reason of Failing Ventral Hernia Repair

Abstract: IntroductionVentral Hernia Repair (VHR) has been a challenging surgery during years. Matters moved to mobilizing muscle and closing the abdominal wall. Component Separation Repair (CSR), which required dissection of the fascia of the rectus muscle and closure of the midline linea alba [1]. The goal of ventral hernia repair is to restore abdominal muscle strength and abdominal wall function [2,3]. The muscle component of the ventral hernia is one of many variables affecting the abdominal wall to contribute to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…These observations, were emphasized by our tensile experiments, where we showed that a thicker elastic material holds more weight than a thinner one despite similar length (P<0.0001) [27]. This gives us a way to compare different materials based upon the same cross-sectional area.…”
Section: Discussionmentioning
confidence: 65%
“…These observations, were emphasized by our tensile experiments, where we showed that a thicker elastic material holds more weight than a thinner one despite similar length (P<0.0001) [27]. This gives us a way to compare different materials based upon the same cross-sectional area.…”
Section: Discussionmentioning
confidence: 65%